2015
DOI: 10.3920/jiff2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different growing substrates and processing on the nutrient composition of black soldier fly larvae destined for animal feed

Abstract: Because of the ongoing depletion of fish stocks and thus continuously rising prices for fish meal, substitution possibilities are in demand. However, since alternate protein sources from plants are mostly of lower protein quality, feedstuff produced from the black soldier fly (BSF) larvae, Hermetia illucens, are considered promising alternatives. Hence, this study investigated the influence of different growing substrates on the crude nutrient and mineral composition of BSF larvae. The three tested substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
213
11
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(270 citation statements)
references
References 16 publications
33
213
11
13
Order By: Relevance
“…The survival rate and feed conversion ratio were not significantly different among all groups ( (Kroeckel et al, 2012;Webster et al, 2016). This discrepancy could be related to differences in life stage of insects and fish species in these studies (Tschirner & Simon, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The survival rate and feed conversion ratio were not significantly different among all groups ( (Kroeckel et al, 2012;Webster et al, 2016). This discrepancy could be related to differences in life stage of insects and fish species in these studies (Tschirner & Simon, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…However, other studies on turbot ( Scophthalmus maximus L.) and Nile tilapia ( Oreochromis niloticus L.) indicated that including BSF larvae into their diet significantly reduced their growth performance (Kroeckel et al, ; Webster et al, ). This discrepancy could be related to differences in life stage of insects and fish species in these studies (Tschirner & Simon, ).…”
Section: Discussionmentioning
confidence: 80%
“…We find that larval crude protein content is higher when dietary P‐content is lower (P10 and P17). This is in line with the findings of Barragan‐Fonseca et al () and Tschirner & Simon () who report that body crude protein content is higher in larvae fed on the diet with the lowest crude protein content. However, it is also argued that this content has been overestimated so far by approximately 20% as a result of the presence of nonprotein nitrogen in insects (Janssen et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The total final biomass (larvae + prepupae) and the residual rearing substrate were also weighed. The following parameters were then calculated: larval mortality (LM) sans-serifLM=[sans-serifinitial number of larvae ]()sans-seriffinal number of larvae+sans-serifnumber of prepupae /sans-serifinitial number of larvae×sans-serif100; growth rate (GR), readapted for this research substituting prepupal body weight (g) with larva body weight (g) sans-serifGR=(sans-seriflarva average final body weight0.25em()g )sans-seriflarval initial body weight0.25em()g/sans-serifdays of trial0.25em()d; substrate reduction (SR) sans-serifSR=[()sans-serifdistributed substrate0.25em()gsans-serifresidual substrate0.25em()g ]/sans-serifdistributed substrate0.25em()g×sans-serif100; waste reduction index (WRI) WRI=WR/W/days of trialsans-serifd×100 …”
Section: Methodsmentioning
confidence: 99%